2006
DOI: 10.1016/j.ymeth.2005.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex bead array assays: Performance evaluation and comparison of sensitivity to ELISA☆

Abstract: The measurement of soluble cytokines and other analytes in serum and plasma is becoming increasingly important in the study and management of many diseases. As a result, there is a growing demand for rapid, precise, and cost-effective measurement of such analytes in both clinical and research laboratories. Multiplex bead array assays provide quantitative measurement of large numbers of analytes using an automated 96-well plate format. ELISAs (enzyme linked immunosorbent assay) have long been the standard for q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
409
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(430 citation statements)
references
References 25 publications
16
409
0
5
Order By: Relevance
“…We could also take in consideration as a limitation the detection sensitivity of multiplexed immunoassays. It was shown that while multiplexed immunoassays have sensitivity comparable to conventional ELISA, it is possible that the robustness may vary among different multiplex bead arrays (29).…”
Section: Discussionmentioning
confidence: 99%
“…We could also take in consideration as a limitation the detection sensitivity of multiplexed immunoassays. It was shown that while multiplexed immunoassays have sensitivity comparable to conventional ELISA, it is possible that the robustness may vary among different multiplex bead arrays (29).…”
Section: Discussionmentioning
confidence: 99%
“…Serum is a complex mix of proteins that may non-specifically bind to microspheres -known as matrix effects (Elshal and McCoy, 2006). These matrix effects can interfere with the performance of a xMAP® assay and may be observed as poor bead recovery, instrumentation clogging, low signals, or variable results.…”
Section: Optimal Sample Preparation For Custom Pentaplex Xmap® Assaymentioning
confidence: 99%
“…The sensitivity of each analyte, based on the lower-used standard, is as follows: Akt (0.2 ng/ml), HSP27 phospho-Ser 82 (5.2 U/ ml), HSP27 phospho-Ser 15 (3.4 U/ml), HSP40 (0.2 ng/ml), HSP60 (3.4 ng/ml), HSP70 (0.2 ng/ml), HSP90-α (0.3 ng/ ml), and Akt phospho-Ser473 (2.0 U/ml). 8 For the analysis we used FACSCalibur Flow Cytometer equipped with 2 lasers (488 and 635 nm) and 6 parameters (Fsc, Ssc, and FL1-FL4).…”
Section: Multibead Analysis Proceduresmentioning
confidence: 99%